Psychodynamics in the Protection of Intangible Cultural Heritage: Theory and Practice - Changqing Fan (Art and Society, 2025)
The protection and inheritance of Intangible Cultural Heritage (ICH) is not only an important task for cultural transmission, but also closely related to the psychological state of the bearers. This study explores the psychological challenges faced by bearers in the protection process of ICH and their impact on cultural transmission from the perspective of psychodynamics. Through literature review, case analysis, and field research, this study deeply analyzes the psychological factors of bearers, such as psychological motivation, emotional investment, social support, and cultural confidence, and constructs a psychodynamic model. The study finds that the psychological state of bearers directly affects the sustainability and enthusiasm of their transmission behaviors. Based on this, this paper proposes psychological support strategies for bearers, including establishing a psychological support system, enhancing cultural confidence, and providing policy and social support, aiming to provide new theoretical basis and practical guidance for the protection of ICH. The results show that the application of psychodynamics can effectively enhance the psychological resilience of bearers and promote the sustainable transmission of ICH.